The Influence of Motivation and Work Discipline on Employee Performance in a National Private Company - Oktavia, Citra Dwi; Sudinta, Heru; Priyono, Agung (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to determine and analyze the influence of motivation and work discipline on employee performance in a National Private Company. Human resources (HR) are considered a crucial asset in achieving company goals, and employee performance is significantly influenced by motivation and work discipline. The method used in this study was a quantitative approach using a survey technique. The study population consisted of 37 employees in a National Private Company. Data were obtained through a questionnaire designed to measure employee motivation, work discipline, and performance. Data analysis was conducted using multiple linear regression to test the proposed hypotheses. The results showed that work motivation has a positive and significant influence on employee performance. Work discipline also showed a positive and significant influence on employee performance. Motivation and work discipline simultaneously influence employee performance. Based on these findings, it can be concluded that motivation and work discipline have a significant influence on employee performance at Private company . Therefore, it is recommended that the company continue to strive to improve employee motivation and work discipline to achieve more optimal performance.